Het christendom: een rem op de ontwikkeling van de samenleving? - Dekker, Gerard (Religie & Samenleving, 2012)
Whereas formerly Christianity has promoted the development of society, nowadays it functions more as an obstacle in this respect. In this short essay the author tries to answer the question when and by which causes Christianity has taken up this position.